2018
DOI: 10.3892/etm.2018.6128
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between dendritic cells and T lymphocytes in pathogenesis of nasal polyps

Abstract: The aim of the present study was to investigate the functional status of dendritic cells (DCs) in nasal polyps (NP) and their interactions with T lymphocytes. The interactions between DC and T lymphocytes in the pathogenesis of NP was also studied. The expression of cluster of differentiation (CD)1a and CD83 in NP was detected using immunohistochemistry and the ratio of CD83 DC/CD1a+DC was counted. The distribution of DCs in NP and normal inferior turbinate mucosa (nITM) was evaluated using double immunostaini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…In our study, we screened for biomarkers of DCs, of these, both CD163 and NR4A1 were highly expressed early in CRSwNP, and CD163+ DCs was shown to correlate with the activation of naïve T cells early in the disease. 44 Lin et al 45 reported a substantial increase in the number of DCs in individuals with NP, which could lead to the activation of B7-1 (CD80) and B7-2 (CD86) expression through their interaction with CD40L on T cells. DC-expressed B7 molecules can activate T cells through the CD28/CTLA-4 pathway, and numerous studies have implicated a collaborative interaction involving DCs and CD4+ T cells in antigen presentation during the immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we screened for biomarkers of DCs, of these, both CD163 and NR4A1 were highly expressed early in CRSwNP, and CD163+ DCs was shown to correlate with the activation of naïve T cells early in the disease. 44 Lin et al 45 reported a substantial increase in the number of DCs in individuals with NP, which could lead to the activation of B7-1 (CD80) and B7-2 (CD86) expression through their interaction with CD40L on T cells. DC-expressed B7 molecules can activate T cells through the CD28/CTLA-4 pathway, and numerous studies have implicated a collaborative interaction involving DCs and CD4+ T cells in antigen presentation during the immune response.…”
Section: Discussionmentioning
confidence: 99%
“…DC-expressed B7 molecules can activate T cells through the CD28/CTLA-4 pathway, and numerous studies have implicated a collaborative interaction involving DCs and CD4+ T cells in antigen presentation during the immune response. 45 , 46 This process of antigen presentation operates bidirectionally, involving DCs facilitating T cell activation while concurrently receiving activation signals from T cells. Notably, T cells exhibit heightened expression of CD80/CD86 on their surfaces during this interaction and undergo reduced adhesion and phagocytosis.…”
Section: Discussionmentioning
confidence: 99%
“…NPs are a common nasal inflammatory disease with regional differences. The pathological features of NPs are characterized by the infiltration of multiple types of inflammatory cells and mixed patterns of T cell response [ 18 ]. According to the European position paper on rhinosinusitis and nasal polyps 2020, it is generally recognized that chronic rhinosinusitis with nasal polyps (CRSwNP) is characterized by infiltration of eosinophils and excessive expression of Th2 cytokines [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…DCs present antigens to naïve T cells and in this way connect innate and AIR. Epithelial cytokines and ILCs activate DCs, leading to pertinent T cell polarization [ 55 , 94 ]. DCs might infiltrate NP tissue and activate T cells by the CD40/CD40L costimulatory molecules [ 94 ].…”
Section: Immunological Response Pathways In Crsmentioning
confidence: 99%
“…Epithelial cytokines and ILCs activate DCs, leading to pertinent T cell polarization [ 55 , 94 ]. DCs might infiltrate NP tissue and activate T cells by the CD40/CD40L costimulatory molecules [ 94 ]. Other studies described increased levels of programmed cell death 1 (PD-1) in CRSwNP [ 95 ] and also programmed cell death 1 ligand 1 (PD-L1) in the case of eosinophilic endotype in Asia population [ 96 ].…”
Section: Immunological Response Pathways In Crsmentioning
confidence: 99%